Peningkaatan Keaktifan Belajar Peserta Didik pada Mata Pelajaran PPKn melalui Model Pembelajaran Kooperatif Tipe TGT (Team games Tournament) di SMP Negeri 10 Palembang - Wenni Rianti; Sri Artati Waluyati; Ardiansyah Saputra (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The research entitled "Increasing Students' Civic Learning Activeness Through the TGT Type Cooperative Learning Model (Team Games Tournament) in Class VII.1 SMP Negeri 10 Palembang" aims to determine the increase in student learning activeness in class VII.1 SMP Negeri 10 Palembang on PPKn subjects the subject of Working Together and Working Together The subjects of this study were students of class VII.1 Palembang State Middle School for the academic year 2022/2023, a total of 38 people. The method used in this research is Classroom Action Research, carried out in 3 cycles consisting of 6 meetings. Based on the results of the study, it was found that student activity in cycle I was 43.61% (19 people), cycle II student activity was 59.72% (26 people), and cycle III student activity was 69.86% (35 people). Of the three cycles carried out showed an increase in student learning activeness,